Understanding stakeholder pressures in adopting environmental management practices based on stakeholder theory: a review - Abu Seman, Noor Aslinda; Zakuan, Norhayati; Rashid, Umi Kartini; Nasuredin, Juzaimi; Ahmad, Nurazwa (IJR, 2018)
The concept of green business is generated from the emerging of environmental pressures that mainly focused on eliminating negative environmental impacts throughout companies’ activities. This purpose of this paper is to review and provide understanding on the stakeholder pressures based on stakeholder theory in driving organization to implement any environmental management practices such as green supply chain management and green innovation. This paper concludes by suggesting the stakeholder theory can be as an underlying theory in supporting the connection between the implementation of an environmental management practices and organizational performance.